DEVELOPMENT OF REGIONAL TOURISM RESOURCES: CURRENT OPPORTUNITIES AND PROSPECTS - Shaymanova Nigora Yusupovna (American Journals, 2025)
Regional tourism resources, including natural, cultural, and historical objects, are an important component of the tourism industry. These resources play a significant role in developing the region's economy, increasing employment, and preserving the national heritage. This article analyses the existing potential of regional tourism resources and their future development prospects.
Keywords: Tourism resources, cultural tourism, recreational resources.